Trust, happiness, and households’ financial decisions - Delis, Manthos D.; Mylonidis, Nikolaos (Journal of Financial Stability, 2015)
A recent line of research highlights trust as an important element guiding the decision of households to invest into risky financial assets and insurance products. This paper contributes to this literature by identifying happiness as another key driver of the same decision. Using detailed survey data from a sample of Dutch households, we show that the impact of happiness on households’ financial decisions works in the opposite direction and is more economically important compared to trust. Specifically, happiness leads to a lower probability of investing into risky financial assets and having insurance, while trust has the usual positive effect found in the literature. Furthermore, the negative effect of happiness on the ownership of risky financial assets is about 6% higher compared to the positive equivalent of trust. Similarly, the negative effect of happiness on the ownership of insurance is 3% higher than the positive effect of trust.